(untitled) (International Journal of Nursing Education, 2020)
Background: Transport of emergency patients requires special attention because it has unexpected eventrisks. The vulnerable emergency department situation with complex cases, limited resources and multidiscipline makes the transfer risky. The emergency department patients that are worth to be transferred toinpatient rooms sometimes must wait until the referred rooms and their equipment are ready. Critical patientsare vulnerable to any worsening condition due to acceleration or deceleration of movements. This researchaims to find out the correlations among the nurses’ experiences, hemodynamics monitoring and equipmentpreparation with unexpected things during transport of Emergency Patients to the Critical Care Unit.Method: This quantitative study uses perspective-observational design. The sample consisted of 151emergency patient transfer processes (the Emergency Department patients) that were transported to theCritical Care Unit. The ages of the sample are older than 16-year-old. The exclusion criteria are patientspassing away in the Emergency Department or referred to other hospitals. The numerical data were analyzedby the Eta test while the categorical data were analyzed by Cramer’s V test.Results: From 151 observed patients, 119 patients experienced unexpected events. The bivariate analysisshows correlation between transport time and unexpected event (F = 10.8, F table = 2.67, r = 0.425).However, there is no correlation between boarding time in the Emergency Department to unexpected events(p = 0.087, r = 0.208).Conclusion: Longer transport time leads to a higher risk of unexpected event occurrence. The companionofficers should be able to prepare the patients properly, to ensure the routes of transport to be free, to promotestrict monitoring during the transport process.